Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
The answer is B
Step-by-step explanation:
f(x) = -3x - 5
g(x) = 4x - 2
= -3x - 5 - (4x - 2)
= -7x - 3
Answer:
B. -7x - 3
Step-by-step explanation:
(f - g)(x) = f(x) - g(x)
f(x): -3x - 5
g(x): 4x - 2
f(x) - g(x) = (-3x - 5) - (4x - 2)
= -3x - 5 - 4x + 2
= (-3x - 4x) + (- 5 + 2)
= (-7x) + (-3)
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.